Correlation of neonatal birth weight with other anthropometric measurements - A cross-sectional study - Chaudhuri, Saugata; Hota, Moumita (Indian Journal of Child Health, 2018)
Background: About 60–80% of neonatal deaths are due to low birth weight (LBW